A catalyst and its preparation method and application
By supporting Co3O4 nanoparticles and MnO2 nanoparticles on nitrogen-doped porous carbon support and optimizing calcining conditions, the existing Co-based catalysts have been solved, and the specific surface area, few active sites and poor stability are achieved, and efficient catalysis is achieved Oxidation activity and low cost catalyst preparation.
Patent Information
- Application Number
- CN202411719281.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The existing Co-based catalysts have defects such as small specific surface area, few active sites, poor stability, and poor catalytic oxidation activity, resulting in high costs and limited application.
Nitrogen-doped porous carbon is used as a support to support Co3O4 nanoparticles and MnO2 nanoparticles, among which Co3O4 nanoparticles are hollow structures. The calcination conditions are optimized to improve the specific surface area and active sites of the catalyst by calcining preparation method of MnCoZn-ZIF material.
The catalyst has achieved a large specific surface area, many active sites, high catalytic oxidation activity and good stability, which reduces the content of Co3O4 nanoparticles and reduces the preparation cost of the catalyst.
Smart Images

Figure CN119186624B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and relates to a catalyst and a preparation method and application thereof. Background Art
[0002] The exhaust gas emitted by steel mills, power plants, etc. contains a large amount of carbon monoxide (CO), which is harmful to human health and the environment. At present, CO catalytic oxidation technology is usually used to treat carbon monoxide exhaust gas. CO is converted into carbon dioxide (CO2) through a catalyst, which can effectively reduce the CO content in the exhaust gas. This technology can be applied in air purification, steel sintering exhaust gas and other fields. It can be seen that catalysts are the key to CO catalytic oxidation technology. Commonly used catalysts include precious metal catalysts and non-precious metal catalysts. Precious metal catalysts use precious metals such as platinum (Pt), palladium (Pd), gold (Au) and ruthenium (Ru) as active components. This type of catalyst has high activity and stability, but due to the high cost of raw materials and complex preparation process, the cost of precious metal catalysts is high, which limits their application and promotion.
[0003] Non-precious metal catalysts usually use non-precious metal gold oxides such as cobalt tetraoxide (Co3O4), cerium dioxide (CeO2), and manganese dioxide (MnO2) as active components. The Co-O bond energy in Co3O4 is low and has strong adsorption properties for the reaction gas. Therefore, Co-based catalysts containing Co3O4 have higher CO catalytic oxidation activity. However, in order to improve the catalytic oxidation activity, the content of Co3O4 is usually increased in existing Co-based catalysts. Compared with other non-precious metals, the price of Co and its oxides is higher, which also leads to the existing Co-based catalysts still having the defect of high cost. In addition, existing Co-based catalysts also have defects such as small specific surface area, few active sites, and poor stability, making it difficult to obtain excellent catalytic performance. For example, some researchers have proposed a MOF-derived Co / MnO xThe preparation method of the doped oxide supported nickel foam catalyst is to first grow CoMn-MOF-74 in situ on nickel foam, and then calcine it in air atmosphere to obtain Co / MnOx doped oxide supported nickel foam catalyst, which has the following defects: (a) the CoMn-MOF-74 used does not contain Zn, so no micropores are formed during the calcination process, resulting in a small specific surface area and few active sites of the prepared Co / MnOx doped oxide, which is not conducive to improving the activity of the catalyst and the mass transfer rate of the reactants; (b) the prepared Co3O4 is solid, resulting in few exposed catalytic active sites and a small effective contact area with the reactants, which is not conducive to improving the activity of the catalyst and the mass transfer rate of the reactants; (c) the nickel foam is used as a carrier, does not contain nitrogen, cannot adjust the electronic structure of the catalyst, is difficult to effectively activate oxygen, and is not conducive to improving the catalytic activity of the catalyst. In addition, the pretreatment process of nickel foam is complicated, which is not conducive to industrial scale-up production.
[0004] Therefore, obtaining a catalyst that reduces the Co3O4 content while ensuring excellent catalytic performance is of great significance for reducing the preparation cost of the catalyst and promoting its widespread use in CO catalytic oxidation technology. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a catalyst with low cost, large specific surface area, multiple active sites, high catalytic oxidation activity and good stability, as well as a preparation method and application thereof.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] A catalyst comprises nitrogen-doped porous carbon, on which Co3O4 nanoparticles and MnO2 nanoparticles are loaded; the Co3O4 nanoparticles are hollow structures.
[0008] The above catalyst is further improved in that the average particle size of the Co3O4 nanoparticles is 9 nm to 16 nm.
[0009] The above catalyst is further improved, and the catalyst also satisfies at least one of the following conditions (1.1) to (1.3):
[0010] (1.1) The mass percentage of Co in the catalyst is 25 wt% to 35 wt%;
[0011] (1.2) The mass percentage of Mn in the catalyst is 3.5 wt% to 12 wt%;
[0012] (1.3) The specific surface area of the catalyst is 410 m 2 / g~470 m 2 / g.
[0013] The above catalyst is further improved in that the mass percentage of Co in the catalyst is 25 wt% to 35 wt%, and the mass percentage of Mn is 3.5 wt% to 12 wt%.
[0014] The above catalyst is further improved in that the specific surface area of the catalyst is 410 m 2 / g~470 m 2 / g.
[0015] As a general technical concept, the present invention also provides a method for preparing a catalyst, comprising the following steps:
[0016] S1. preparing MnCoZn-ZIF material;
[0017] S2, calcining the MnCoZn-ZIF material for the first time in an inert atmosphere at a temperature of 800° C. to 1000° C. to obtain an intermediate material;
[0018] S3. calcining the intermediate material for the second time in an oxygen-containing atmosphere at a temperature of 250° C. to 500° C. to obtain a catalyst.
[0019] The above preparation method is further improved, wherein the preparation method of the catalyst also satisfies at least one of the following conditions (2.1) to (2.6):
[0020] (2.1) The temperature of the first calcination is 850°C to 950°C;
[0021] (2.2) The first calcination time is 2 h to 4 h;
[0022] (2.3) The inert atmosphere includes at least one of nitrogen and argon;
[0023] (2.4) The temperature of the second calcination is 350°C to 450°C;
[0024] (2.5) The second calcination time is 2 h to 5 h;
[0025] (2.6) The oxygen-containing atmosphere includes at least one of oxygen and air.
[0026] The above preparation method is further improved, in step S2, the temperature of the first calcination is 850°C to 950°C, the time of the first calcination is 2 h to 4 h, and the inert atmosphere includes at least one of nitrogen and argon.
[0027] The above preparation method is further improved, in step S3, the temperature of the second calcination is 350°C to 450°C, the time of the second calcination is 2 h to 5 h, and the oxygen-containing atmosphere includes at least one of oxygen and air.
[0028] The above preparation method is further improved, and before the second calcination, the intermediate material is further treated as follows: the intermediate material is washed with an acidic solution; the pH value of the acidic solution is 1-4.
[0029] The above preparation method is further improved, in step S1, the preparation method of the MnCoZn-ZIF material comprises the following steps:
[0030] S1-1, preparing a first solution by combining 2-methylimidazole and a first solvent; preparing a second solution by combining a manganese source, a cobalt source, a zinc source and a second solvent;
[0031] S1-2, mixing the first solution and the second solution to react, to prepare the MnCoZn-ZIF material.
[0032] The above preparation method is further improved, and the preparation method of the MnCoZn-ZIF material also satisfies at least one of the following conditions (3.1) to (3.11):
[0033] (3.1) The molar ratio of manganese ions in the manganese source to cobalt ions in the cobalt source is 0.15 to 0.25:1;
[0034] (3.2) The molar ratio of cobalt ions in the cobalt source to zinc ions in the zinc source is 0.3 to 0.4:1;
[0035] (3.3) The molar ratio of the 2-methylimidazole to the cobalt ions in the cobalt source is 5 to 20:1;
[0036] (3.4) The manganese source includes at least one of manganese nitrate tetrahydrate, manganese sulfate monohydrate and manganese acetate trihydrate;
[0037] (3.5) The cobalt source includes at least one of cobalt nitrate hexahydrate and cobalt acetate tetrahydrate;
[0038] (3.6) The zinc source includes at least one of zinc nitrate hexahydrate and zinc acetate dihydrate;
[0039] (3.7) The first solvent includes at least one of methanol, ethanol and water;
[0040] (3.8) The second solvent includes at least one of methanol, ethanol and water;
[0041] (3.9) The reaction is carried out at a pressure of 0.05 MPa to 0.2 MPa;
[0042] (3.10) The reaction temperature is 20 ℃ to 50 ℃; the reaction time is 1 h to 24 h;
[0043] (3.11) After the reaction is completed, the following treatment is further included: the reaction solution obtained by the reaction is centrifuged, washed and dried to obtain MnCoZn-ZIF material.
[0044] The above preparation method is further improved, in step S1-1, the molar ratio of manganese ions in the manganese source to cobalt ions in the cobalt source is 0.15-0.25:1, the molar ratio of cobalt ions in the cobalt source to zinc ions in the zinc source is 0.3-0.4:1, and the molar ratio of 2-methylimidazole to cobalt ions in the cobalt source is 5-20:1.
[0045] The above preparation method is further improved, in step S1-1, the manganese source includes at least one of manganese nitrate tetrahydrate, manganese sulfate monohydrate and manganese acetate trihydrate; the cobalt source includes at least one of cobalt nitrate hexahydrate and cobalt acetate tetrahydrate; the zinc source includes at least one of zinc nitrate hexahydrate and zinc acetate dihydrate; the first solvent includes at least one of methanol, ethanol and water; the second solvent includes at least one of methanol, ethanol and water.
[0046] The above preparation method is further improved, in step S1-2, the reaction is carried out at a pressure of 0.05 MPa to 0.2 MPa; the reaction temperature is 20 ℃ to 50 ℃; the reaction time is 1 h to 24 h; after the reaction is completed, the following treatment is also included: centrifuging, washing and drying the reaction solution to obtain MnCoZn-ZIF material
[0047] The above preparation method is further improved, in step S2, the intermediate material includes nitrogen-doped porous carbon, and the nitrogen-doped porous carbon is loaded with Co nanoparticles and Mn nanoparticles.
[0048] The above preparation method is further improved, in step S3, the catalyst includes nitrogen-doped porous carbon, and the nitrogen-doped porous carbon is loaded with Co3O4 nanoparticles and MnO2 nanoparticles; the Co3O4 nanoparticles are hollow structures.
[0049] As a general technical concept, the present invention also provides a use of the above catalyst or the catalyst prepared by the above preparation method in the catalytic oxidation of carbon monoxide.
[0050] Compared with the prior art, the advantages of the present invention are:
[0051] (1) In view of the defects of existing Co-based catalysts such as small specific surface area, few active sites, poor stability, and poor catalytic oxidation activity, the present invention provides a catalyst comprising nitrogen-doped porous carbon, on which Co3O4 nanoparticles and MnO2 nanoparticles are loaded, wherein the Co3O4 nanoparticles are hollow structures. In the present invention, with nitrogen-doped porous carbon as a carrier, Co3O4 nanoparticles and MnO2 nanoparticles can be uniformly and firmly loaded on nitrogen-doped porous carbon, so that the catalyst has the advantages of large specific surface area, many active sites and good stability, and the nitrogen-doped porous carbon carrier of the present invention has rich micropores, which is conducive to improving the mass transfer efficiency of reactants on the catalyst surface and the accessibility of catalytic active sites. At the same time, the nitrogen atoms in the nitrogen-doped porous carbon can also effectively activate oxygen, which is conducive to further improving the catalytic oxidation activity of the catalyst. More importantly, under the joint action of Co3O4 nanoparticles and MnO2 nanoparticles, the catalytic oxidation activity of the catalyst can also be significantly improved. Therefore, under the synergistic action of nitrogen-doped porous carbon, Co3O4 nanoparticles and MnO2 nanoparticles, the catalyst can be ensured to have excellent catalytic activity and stability under the premise of reducing the content of Co3O4 nanoparticles. In addition, Co3O4 nanoparticles are hollow structures, which can expose more catalytic active sites, can provide a suitable reaction site for reactants, and then can improve the activity of the catalyst and the mass transfer rate of the reactants. Compared with existing conventional Co-based catalysts, the catalyst of the present invention has the advantages of low cost, large specific surface area, multiple active sites, high catalytic oxidation activity, and good stability. When used for the catalytic oxidation of carbon monoxide, it can oxidize carbon monoxide into carbon dioxide more quickly and thoroughly, which is of great significance for achieving effective purification of carbon monoxide tail gas.
[0052] (2) The present invention also provides a method for preparing a catalyst, using MnCoZn-ZIF material as a raw material, first calcining the MnCoZn-ZIF material in an inert atmosphere at a temperature of 800°C to 1000°C, during the first calcination process, the MnCoZn-ZIF material is carbonized to form a carbon material, and under the action of 2-methylimidazole, nitrogen doping of the carbon material can be achieved to form a nitrogen-doped carbon material, thereby obtaining a nitrogen-doped porous carbon carrier. More importantly, during the first calcination process, the organic ligand (i.e., 2-methylimidazole) with a lower thermal decomposition temperature in the MnCoZn-ZIF material is first carbonized to form inorganic carbon, and this inorganic carbon has reducing properties, so that the cobalt ions, manganese ions and zinc ions can be reduced. The nanoparticles are reduced to metallic cobalt nanoparticles, metallic manganese nanoparticles and metallic zinc nanoparticles, respectively. Furthermore, the metallic zinc nanoparticles with low boiling point volatilize during the first calcination process, thereby forming abundant micropores in situ in the nitrogen-doped carbon material, while the metallic cobalt nanoparticles and metallic manganese nanoparticles with high boiling point are uniformly and firmly loaded on the nitrogen-doped porous carbon. In addition, thanks to the "fence" effect of the metallic zinc nanoparticles, there is no obvious agglomeration of the two metallic nanoparticles of cobalt and manganese, so the particle size is small, providing a basis for the preparation of small-particle Co3O4 nanoparticles and MnO2 nanoparticles. On this basis, the product of the first calcination (i.e., the intermediate material) is used as a raw material, and the intermediate material is calcined for the second time in an oxygen-containing atmosphere at a temperature of 250°C to 500°C. During the second calcination process, the metal cobalt nanoparticles and the metal manganese nanoparticles are in-situ oxidized into Co3O4 nanoparticles and MnO2 nanoparticles, and thanks to the Kirkendall effect, the Co3O4 nanoparticles form a hollow structure, thereby preparing a catalyst with a large specific surface area, many active sites, high catalytic oxidation activity, and good stability. In addition, after calcining the MnCoZn-ZIF material as a raw material twice, the obtained catalyst still retains the dodecahedral structure of the MnCoZn-ZIF material, that is, the obtained catalyst also has a dodecahedral structure, and this regular polyhedral structure is conducive to the catalytic reaction. In addition, the preparation method of the present invention also has the advantages of simple process, convenient operation, low cost, etc., is suitable for large-scale preparation, and is convenient for industrial application.
[0053] (3) In the preparation method of the present invention, the conditions of the first calcination and the second calcination are further optimized. Specifically, by optimizing the temperature of the first calcination to 850 ℃ to 950 ℃ and the time to 2 h to 4 h, not only can the cobalt ions and manganese ions be fully reduced to metal cobalt nanoparticles and metal manganese nanoparticles, but also the metal zinc nanoparticles can be fully volatilized, which is more conducive to the rational utilization of raw materials and the formation of a porous catalyst with richer micropores; at the same time, by optimizing the temperature of the second calcination to 350 ℃ to 450 ℃ and the time to 3 h to 5 h, not only can the metal cobalt nanoparticles and metal manganese nanoparticles in the intermediate material be fully oxidized, so that the metal cobalt and metal manganese are converted into Co3O4 nanoparticles and MnO2 nanoparticles as much as possible, but also the Co3O4 nanoparticles can be promoted to form a hollow structure, further improving the performance of the catalyst. In particular, when the time of the second calcination is less than 2 h, the nanoparticles cannot form a complete hollow structure, and when the calcination time is greater than 5 h, the energy consumption will increase and the structure of the catalyst may even collapse.
[0054] (4) In the preparation method of the present invention, the molar ratio of manganese ions in the manganese source to cobalt ions in the cobalt source is optimized to be 0.15 to 0.25:1. When the MnCoZn-ZIF material prepared in this way is used to prepare a catalyst, the content of Co3O4 nanoparticles and MnO2 nanoparticles in the obtained catalyst can be further regulated, thereby optimizing the synergistic catalytic effect between the above two types of Co3O4 nanoparticles and MnO2 nanoparticles, compensating for the adverse effect of reducing the content of Co3O4 nanoparticles on the catalyst performance, and thus improving the performance of the catalyst. In particular, when the above molar ratio is less than 0.15:1, the content of MnO2 nanoparticles in the catalyst is low, there is no obvious synergistic effect between Co3O4 nanoparticles and MnO2 nanoparticles, and the activity of the catalyst is low. When the molar ratio is greater than 0.25:1, the content of Co3O4 nanoparticles is high, more cobalt sources are used, and the raw material cost of the catalyst is increased.
[0055] (5) In the preparation method of the present invention, the molar ratio of cobalt ions in the cobalt source to zinc ions in the zinc source is optimized to be 0.3 to 0.4:1. When the MnCoZn-ZIF material prepared in this way is used to prepare a catalyst, the size of the Co3O4 nanoparticles and the MnO2 nanoparticles in the obtained catalyst can be more effectively regulated, while ensuring that the catalyst has a high micropore content, thereby improving the performance of the catalyst. In particular, when the above molar ratio is less than 0.3:1, due to the high zinc ion content, the content of the active components Co3O4 nanoparticles and MnO2 nanoparticles in the catalyst is low, and due to the high zinc ion content, the micropore content is also high, which may cause the structure of the nitrogen-doped porous carbon carrier to collapse, so the catalytic activity and stability of the catalyst will deteriorate; when the above molar ratio is greater than 0.4:1, the zinc ion content is low and the cobalt ion content is high. During the first calcination process, the reduced metal cobalt nanoparticles and metal manganese nanoparticles are prone to agglomeration, which reduces the catalytic activity of the catalyst.
[0056] (6) In the preparation method of the present invention, the molar ratio of 2-methylimidazole to cobalt ions in the cobalt source is optimized to 5 to 20:1, thereby being able to prepare MnCoZn-ZIF materials with good morphology, high crystallinity and high specific surface area, providing a precursor that meets the requirements for the subsequent preparation of catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0058] Figure 1 1 is the XRD diagram of the catalyst prepared in Example 1, Example 8 and Example 9 of the present invention.
[0059] Figure 2 This is a SEM image of the catalyst prepared in Example 1 of the present invention.
[0060] Figure 3 This is a TEM image of Co3O4 nanoparticles in the catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0061] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments of the specification, but the protection scope of the present invention is not limited thereby. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0062] The "range" disclosed in the present invention can be defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of the end values, and any end value can be included or excluded independently, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a specific parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are also listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present invention, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, wherein a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in this article, and "0-5" is just an abbreviation of these numerical combinations.
[0063] In the present invention, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0064] If not otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form a new technical solution.
[0065] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present invention. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. Reference to "implementations" herein has a similar understanding.
[0066] Those skilled in the art will appreciate that, in the methods of various embodiments or examples, the order in which each step is written does not mean a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present invention can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0067] In the present invention, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.
[0068] In the present invention, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel solutions of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "option" is independent.
[0069] The current Co-based catalysts have the disadvantages of being difficult to balance cost, poor catalytic oxidation activity and poor stability. Based on this, the present invention provides a catalyst and a preparation method and application thereof, aiming to reduce the cost of the catalyst while ensuring excellent catalytic performance.
[0070] In a first aspect, the present invention provides a catalyst comprising nitrogen-doped porous carbon, on which Co3O4 nanoparticles and MnO2 nanoparticles are loaded, and the Co3O4 nanoparticles are hollow structures.
[0071] Understandably, nanoparticles refer to ultrafine particles with a size between 1 nm and 100 nm. Hollow structure, also known as hollow structure, refers to a material or particle with a cavity inside. Further, in the present invention, the Co3O4 nanoparticles are hollow structures, which means that the Co3O4 nanoparticles have a cavity inside.
[0072] The catalyst in the above-mentioned embodiment uses nitrogen-doped porous carbon as a carrier, and Co3O4 nanoparticles and MnO2 nanoparticles can be uniformly and firmly loaded on the nitrogen-doped porous carbon, so that the catalyst has the advantages of large specific surface area, multiple active sites and good stability. Moreover, the above-mentioned nitrogen-doped porous carbon carrier has abundant micropores, which is beneficial to improve the mass transfer efficiency of reactants on the catalyst surface and the accessibility of catalytic active sites. At the same time, the nitrogen atoms in the nitrogen-doped porous carbon can also effectively activate oxygen, which is beneficial to further improve the catalytic oxidation activity of the catalyst. More importantly, under the joint action of Co3O4 nanoparticles and MnO2 nanoparticles, the catalytic oxidation activity of the catalyst can also be significantly improved. Therefore, under the synergistic action of nitrogen-doped porous carbon, Co3O4 nanoparticles and MnO2 nanoparticles, the catalyst can be ensured to have excellent catalytic activity and stability while reducing the content of Co3O4 nanoparticles.
[0073] Furthermore, in the above-mentioned catalyst, the Co3O4 nanoparticles have a hollow structure, which can expose more catalytic active sites, provide a suitable reaction site for the reactants, and thus improve the catalytic activity of the catalyst and the mass transfer rate of the reactants.
[0074] In some embodiments, the average particle size of the Co3O4 nanoparticles is 9 nm to 16 nm. As an example, the average particle size of the Co3O4 nanoparticles may be 9 nm, 9.5 nm, 10 nm, 10.5 nm, 11 nm, 11.5 nm, 12 nm, 12.5 nm, 13 nm, 13.5 nm, 14 nm, 14.5 nm, 15 nm, 15.5 nm, 16 nm, or may be within the range of any two of the above point values as end values, optionally 10 nm to 15 nm. When the average particle size of the Co3O4 nanoparticles is 9 nm to 16 nm, there is no obvious agglomeration of the Co3O4 nanoparticles, and they can be more firmly loaded on the nitrogen-doped porous carbon support and are not easy to fall off, thereby effectively improving the catalytic activity and structural stability of the catalyst.
[0075] In some embodiments, the average particle size of the MnO2 nanoparticles is 9 nm to 16 nm. As an example, the average particle size of the MnO2 nanoparticles may be 9 nm, 9.5 nm, 10 nm, 10.5 nm, 11 nm, 11.5 nm, 12 nm, 12.5 nm, 13 nm, 13.5 nm, 14 nm, 14.5 nm, 15 nm, 15.5 nm, 16 nm, or may be within the range of any two of the above point values as end values, optionally 10 nm to 15 nm. When the average particle size of the MnO2 nanoparticles is 9 nm to 16 nm, there is no obvious agglomeration of the MnO2 nanoparticles, and the MnO2 nanoparticles can be more firmly loaded on the nitrogen-doped porous carbon carrier, and are not easy to fall off, so they can more effectively cooperate with the Co3O4 nanoparticles to enhance the catalytic activity of the catalyst.
[0076] In some embodiments, the average particle size of the Co3O4 nanoparticles is 9 nm to 16 nm, and the average particle size of the MnO2 nanoparticles is 9 nm to 16 nm. Understandably, the average particle sizes of the Co3O4 nanoparticles and the MnO2 nanoparticles are each independently selected from 9 nm to 16 nm. The two nanoparticles of the above-mentioned specific average particle size can not only independently exert excellent catalytic performance, but also have a good synergistic catalytic effect between the two, which can further improve the performance of the catalyst.
[0077] It should be noted that the average particle size of the Co3O4 nanoparticles can be measured by transmission electron microscopy (TEM), and the average value of at least 20 nanoparticle size measurements is taken as the final average particle size. It is understandable that the average particle size can also be measured by other standard or common test methods.
[0078] In some embodiments, the mass percentage of Co in the catalyst is 25 wt% to 35 wt%. It is understandable that Co in the catalyst mainly exists in the form of Co3O4, and the mass percentage of Co in the above catalyst refers to the mass percentage of Co in Co3O4, which can be measured by general testing methods such as plasma emission spectroscopy or atomic absorption spectroscopy. As an example, the mass percentage of Co in the catalyst may be 25 wt%, 25.29 wt%, 25.5 wt%, 26 wt%, 26.5 wt%, 26.9 wt%, 27 wt%, 27.23 wt%, 27.43 wt%, 27.52 wt%, 27.53 wt%, 27.68 wt%, 27.83 wt%, 28wt%, 28.36 wt%, 28.5 wt%, 29 wt%, 29.5 wt%, 30 wt%, 30.5 wt%, 31 wt%, 31.5 wt%, 32 wt%, 32.5 wt%, 33 wt%, 33.42 wt%, 33.5 wt%, 34 wt%, 34.5 wt%, 35 wt%, or it may be within the range consisting of any two of the above point values as end values, optionally 25.29 wt% to 33.42 wt%. When the mass percentage of Co in the catalyst is 25 wt% to 35 wt%, the Co content of the catalyst can be as low as possible while ensuring the catalytic performance, thereby reducing the raw material cost.
[0079] In some embodiments, the mass percentage of Mn in the catalyst is 3.5 wt% to 12 wt%. It is understandable that the Mn in the catalyst is mainly present in the form of MnO2, and the mass percentage of Mn in the above catalyst refers to the mass percentage of Mn in MnO2, which can be measured by common testing methods such as plasma emission spectroscopy or atomic absorption spectroscopy. As an example, the mass percentage of Mn in the catalyst may be 3.5 wt%, 3.89%, 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, 8 wt%, 8.02 wt%, 8.19 wt%, 8.28 wt%, 8.32 wt%, 8.27 wt%, 8.34 wt%, 8.45 wt%, 8.53 wt%, 8.5 wt%, 9 wt%, 9.5 wt%, 10 wt%, 10.5 wt%, 11 wt%, 11.23 wt%, 11.5 wt%, 12 wt%, or it may be within the range consisting of any two of the above point values as end values, optionally 3.89 wt% to 11.23 wt%. When the mass percentage of Mn in the catalyst is 3.5 wt% to 12 wt%, the synergistic catalytic effect between Co3O4 nanoparticles and MnO2 nanoparticles can be fully exerted, which is beneficial to improving the catalytic performance of the catalyst.
[0080] In some embodiments, the catalyst has a specific surface area of 410 m 2 / g~470 m 2 / g. As an example, the specific surface area of the catalyst can be 410 m 2 / g, 413 m 2 / g, 415 m 2 / g, 420 m 2 / g, 425 m 2 / g, 430 m 2 / g, 435 m 2 / g, 440 m 2 / g, 445 m 2 / g, 450 m 2 / g, 455 m 2 / g, 460 m 2 / g, 465 m 2 / g, 466 m 2 / g, 470 m 2 / g, or any two of the above points can be used as the end value within the range, optionally 413 m 2 / g~466 m 2 / g. The specific surface area of the catalyst is 410 m 2 / g~470 m 2 / g, the mass transfer rate of the reactants can be increased, thereby improving the catalytic activity.
[0081] In a second aspect, the present invention provides a method for preparing a catalyst, comprising the following steps S1-S3:
[0082] S1. preparing MnCoZn-ZIF material;
[0083] S2, calcining the MnCoZn-ZIF material for the first time in an inert atmosphere at a temperature of 800°C to 1000°C to obtain an intermediate material;
[0084] S3. The intermediate material is calcined for the second time in an oxygen-containing atmosphere at a temperature of 250° C. to 500° C. to obtain a catalyst.
[0085] ZIF materials (Zeolitic Imidazolate Frameworks) are a type of metal organic framework materials (Metal Organic Frameworks, MOFs for short). MOFs are crystalline porous materials formed by self-assembly of inorganic metals (metal ions or metal clusters) and bridging organic ligands. They are different from inorganic porous materials and general organic complexes, and have both the rigidity of inorganic materials and the flexibility of organic materials. ZIFs are MOFs with zeolite-like structures formed by the reaction of metal ions (such as zinc ions or cobalt ions) with imidazole ligands. Furthermore, the MnCoZn-ZIF material in the present invention refers to MOFs formed by the coordination of manganese ions, cobalt ions and zinc ions with 2-methylimidazole.
[0086] In some embodiments, the temperature of the first calcination is 800° C. to 1000° C. As an example, the temperature of the first calcination may be 800° C., 820° C., 840° C., 850° C., 860° C., 880° C., 900° C., 920° C., 940° C., 950° C., 960° C., 970° C., 980° C., 1000° C., or may be within a range consisting of any two of the above point values as end values.
[0087] In some embodiments, the temperature of the second calcination is 250° C. to 500° C. As an example, the temperature of the second calcination may be 250° C., 260° C., 280° C., 300° C., 320° C., 340° C., 350° C., 353° C., 357° C., 360° C., 362° C., 365° C., 369° C., 371° C., 378° C., 380° C., 385° C., 390° C., 396° C., 400° C., 410° C., 428° C., 436° C., 440° C., 443° C., 448° C., 450° C., 460° C., 480° C., 500° C., or may be within a range consisting of any two of the above point values as end values.
[0088] In the preparation method of the above catalyst, MnCoZn-ZIF material is used as a raw material, and the MnCoZn-ZIF material is first calcined at a temperature of 800°C to 1000°C in an inert atmosphere. During the first calcination process, the MnCoZn-ZIF material is carbonized to form a carbon material, and under the action of 2-methylimidazole, nitrogen doping of the carbon material can be achieved to form a nitrogen-doped carbon material, thereby obtaining a nitrogen-doped porous carbon carrier. More importantly, during the first calcination process, the organic ligand (i.e., 2-methylimidazole) with a lower thermal decomposition temperature in the MnCoZn-ZIF material is first carbonized to form inorganic carbon, and this inorganic carbon has reducing properties, so that cobalt ions and manganese ions can be reduced. and zinc ions are reduced to metallic cobalt nanoparticles, metallic manganese nanoparticles and metallic zinc nanoparticles, respectively. Furthermore, the metallic zinc nanoparticles with low boiling point volatilize during the first calcination process, thereby forming abundant micropores in situ in the nitrogen-doped carbon material, while the metallic cobalt nanoparticles and metallic manganese nanoparticles with high boiling point are uniformly and firmly loaded on the nitrogen-doped porous carbon. In addition, thanks to the "fence" effect of the metallic zinc nanoparticles, there is no obvious agglomeration of the two metallic nanoparticles of cobalt and manganese, so the particle size is small, providing a basis for the preparation of small-particle Co3O4 nanoparticles and MnO2 nanoparticles. On this basis, the product of the first calcination (i.e., the intermediate material) is used as a raw material, and the intermediate material is calcined for the second time at a temperature of 250°C to 500°C and in an oxygen-containing atmosphere. During the second calcination process, metal cobalt nanoparticles and metal manganese nanoparticles are in-situ oxidized into Co3O4 nanoparticles and MnO2 nanoparticles, and thanks to the Kirkendall effect, the Co3O4 nanoparticles form a hollow structure, thereby preparing a catalyst with a large specific surface area, many active sites, high catalytic oxidation activity, and good stability. In addition, after calcining twice with the MnCoZn-ZIF material as the raw material, the obtained catalyst still retains the dodecahedral structure of the MnCoZn-ZIF material, that is, the obtained catalyst also has a dodecahedral structure, and this regular polyhedral structure is conducive to the catalytic reaction. In addition, the preparation method of the present invention also has the advantages of simple process, convenient operation, low cost, etc., is suitable for large-scale preparation, and is convenient for industrial application.
[0089] In some embodiments, the temperature of the first calcination is 850°C to 950°C.
[0090] In some embodiments, the first calcination time may be 2 h to 4 h. As an example, the first calcination time may be 2 h, 2.5 h, 3 h, 3.5 h, 4 h, or within the range of any two of the above point values as end values. Optionally, the first calcination time may be 2.5 h to 3.5 h.
[0091] In the preparation method of the catalyst of the present invention, by optimizing the temperature of the first calcination to 850°C to 950°C and the time to 2 h to 4 h, not only can the cobalt ions and manganese ions be fully reduced to metal cobalt nanoparticles and metal manganese nanoparticles, but the metal zinc nanoparticles can also be further volatilized, which is more conducive to the rational use of raw materials and the formation of a porous catalyst with richer micropores.
[0092] In some embodiments, the inert atmosphere includes at least one of nitrogen and argon. As an example, the inert atmosphere is a nitrogen atmosphere or an argon atmosphere.
[0093] In some embodiments, the heating rate of the first calcination is 2°C / min to 10°C / min. As an example, the heating rate of the first calcination may be 2°C / min, 4°C / min, 5°C / min, 6°C / min, 8°C / min, 9°C / min, 10°C / min, or may be within the range consisting of any two of the above point values as end values. Optionally, the heating rate of the first calcination is 4°C / min to 9°C / min.
[0094] In some embodiments, the second calcination temperature is 350°C to 450°C.
[0095] In some embodiments, the second calcination time is 2 h to 5 h. As an example, the second calcination time can be 2 h, 2.5 h, 3 h, 3.2 h, 3.4 h, 3.5 h, 3.6 h, 4 h, 4.2 h, 4.6 h, 4.8 h, 5 h, or within the range of any two of the above point values as end values. Optionally, the second calcination time is 3 h to 5 h.
[0096] In the preparation method of the catalyst of the present invention, by optimizing the temperature of the second calcination to 350°C to 450°C and the time to 3 hours to 5 hours, not only can the metal cobalt nanoparticles and metal manganese nanoparticles in the intermediate material be fully oxidized, so that the metal cobalt and metal manganese are converted into Co3O4 nanoparticles and MnO2 nanoparticles as much as possible, but also the Co3O4 nanoparticles can be promoted to form a hollow structure, further improving the performance of the catalyst. In particular, when the second calcination time is less than 2 hours, the nanoparticles cannot form a complete hollow structure, and when the calcination time is greater than 5 hours, the energy consumption will increase, and the structure of the catalyst may even collapse.
[0097] It is understandable that the oxygen-containing atmosphere refers to an atmosphere containing oxygen, and there is no specific requirement for the oxygen content. In some embodiments, the oxygen-containing atmosphere includes at least one of oxygen and air.
[0098] In some embodiments, the heating rate of the second calcination is 1°C / min to 5°C / min. As an example, the heating rate of the second calcination may be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, or may be within the range consisting of any two of the above point values as end values. Optionally, the heating rate of the second calcination is 2°C / min to 5°C / min.
[0099] In some embodiments, the intermediate material is further treated as follows before the second calcination: the intermediate material is washed with an acidic solution. The metal zinc nanoparticles remaining on the intermediate material carrier can be removed by acid washing, thereby increasing the micropore content and specific surface area in the catalyst and improving the performance of the obtained catalyst.
[0100] In some embodiments, the intermediate material is pickled with an acidic solution having a pH value of 1 to 4. As an example, the pH value of the acidic solution is 1, 1.5, 2, 2.5, 3, 3.4, 4, or may be within a range consisting of any two of the above point values as end values. Optionally, the pH value of the acidic solution is 2 to 4. It should be noted that the pH value in the present invention refers to the pH at room temperature.
[0101] Further, the acidic solution includes at least one of a hydrochloric acid aqueous solution, a nitric acid aqueous solution and a sulfuric acid aqueous solution.
[0102] In some embodiments, the method for preparing the MnCoZn-ZIF material comprises the following steps:
[0103] S1-1, preparing a first solution by combining 2-methylimidazole and a first solvent; preparing a second solution by combining a manganese source, a cobalt source, a zinc source and a second solvent;
[0104] S1-2, mixing the first solution and the second solution to react and prepare a MnCoZn-ZIF material.
[0105] In some embodiments, the molar ratio of manganese ions in the manganese source to cobalt ions in the cobalt source is 0.15 to 0.25: 1. As an example, the molar ratio of manganese ions in the manganese source to cobalt ions in the cobalt source may be 0.15: 1, 0.16: 1, 0.17: 1, 0.18: 1, 0.19: 1, 0.20: 1, 0.21: 1, 0.22: 1, 0.23: 1, 0.24: 1, 0.25: 1, or within the range of any two of the above point values as end values. Optionally, the molar ratio of manganese ions in the manganese source to cobalt ions in the cobalt source is 0.16: 1 to 0.24: 1.
[0106] In the preparation method of the present invention, by optimizing the molar ratio of manganese ions in the manganese source to cobalt ions in the cobalt source to 0.15 to 0.25:1, the MnCoZn-ZIF material prepared thereby can be used to prepare a catalyst, and the content of Co3O4 nanoparticles and MnO2 nanoparticles in the obtained catalyst can be further regulated, thereby optimizing the synergistic catalytic effect between the above two metal oxides, compensating for the adverse effect of reducing the content of Co3O4 nanoparticles on the catalyst performance, and further improving the performance of the catalyst. In particular, when the above molar ratio is less than 0.15:1, the content of MnO2 nanoparticles in the catalyst is low, there is no obvious synergistic effect between the Co3O4 nanoparticles and the MnO2 nanoparticles, and the activity of the catalyst is low, while when the molar ratio is greater than 0.25:1, the content of Co3O4 nanoparticles is high, more cobalt sources are used, and the raw material cost of the catalyst is increased.
[0107] In some embodiments, the molar ratio of cobalt ions in the cobalt source to zinc ions in the zinc source is 0.3 to 0.4: 1. As an example, the molar ratio of cobalt ions in the cobalt source to zinc ions in the zinc source may be 0.3: 1, 0.32: 1, 0.34: 1, 0.35: 1, 0.36: 1, 0.38: 1, 0.4: 1, or may be within the range formed by any two of the above point values as end values. Optionally, the molar ratio of cobalt ions in the cobalt source to zinc ions in the zinc source is 0.32: 1 to 0.38: 1.
[0108] In the preparation method of the present invention, by optimizing the molar ratio of cobalt ions in the cobalt source to zinc ions in the zinc source to 0.3 to 0.4:1, the MnCoZn-ZIF material prepared thereby can more effectively regulate the size of Co3O4 nanoparticles and MnO2 nanoparticles in the obtained catalyst when used to prepare the catalyst, while ensuring that the catalyst has a high micropore content, thereby facilitating the improvement of the performance of the catalyst. In particular, when the molar ratio is less than 0.3:1, due to the high zinc ion content, the active component Co3O4 nanoparticles and MnO2 nanoparticles in the catalyst have low contents, and due to the high zinc ion content, the micropore content is also high, which may cause the structure of the nitrogen-doped porous carbon carrier to collapse, so that the catalytic activity and stability of the catalyst will deteriorate; when the molar ratio is greater than 0.4:1, the zinc ion content is low and the cobalt ion content is high, and during the first calcination process, the reduced metal cobalt nanoparticles and metal manganese nanoparticles are prone to agglomeration, thereby reducing the catalytic activity of the catalyst.
[0109] In some embodiments, the molar ratio of 2-methylimidazole to cobalt ions in the cobalt source is 5 to 20: 1. As an example, the molar ratio of 2-methylimidazole to cobalt ions in the cobalt source may be 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, 11: 1, 12: 1, 13: 1, 14: 1, 15: 1, 16: 1, 17: 1, 18: 1, 19: 1, 20: 1, or within the range of any two of the above point values as end values. Optionally, the molar ratio of 2-methylimidazole to cobalt ions in the cobalt source is 5: 1 to 10: 1.
[0110] In some embodiments, the manganese source includes at least one of manganese nitrate tetrahydrate, manganese sulfate monohydrate, and manganese acetate trihydrate.
[0111] In some embodiments, the cobalt source includes at least one of cobalt nitrate hexahydrate and cobalt acetate tetrahydrate. As an example, the cobalt source may be cobalt nitrate hexahydrate or cobalt acetate tetrahydrate.
[0112] In some embodiments, the zinc source includes at least one of zinc nitrate hexahydrate and zinc acetate dihydrate. As an example, the zinc source can be zinc nitrate hexahydrate or zinc acetate dihydrate.
[0113] In some embodiments, the first solvent includes at least one of methanol, ethanol, and water. As an example, the first solvent may be methanol, ethanol, or water.
[0114] In some embodiments, the first solvent is a mixed solution of methanol and water, and optionally, the volume ratio of methanol to water in the mixed solution of methanol and water is 0.5 to 5: 1. As an example, the volume ratio of methanol to water in the mixed solution of methanol and water can be 0.5: 1, 1: 1, 1.5: 1, 2: 1, 3: 1, 4: 1, 5: 1.
[0115] In some embodiments, the ratio of the volume of the first solvent to the mass of 2-methylimidazole is (1-20) L: 1 g. As an example, the ratio of the volume of the first solvent to the mass of 2-methylimidazole may be 1 L: 1 g, 2 L: 1 g, 3 L: 1 g, 4 L: 1 g, 5 L: 1 g, 6 L: 1 g, 7 L: 1 g, 10 L: 1 g, 12 L: 1 g, 15 L: 1 g, 18 L: 1 g, 20 L: 1 g.
[0116] In some embodiments, the second solvent includes at least one of methanol, ethanol, and water. As an example, the second solvent may be methanol, ethanol, or water.
[0117] In some embodiments, the second solvent is a mixed solution of methanol and water, and optionally, the volume ratio of methanol to water in the mixed solution of methanol and water is 0.5 to 5: 1. As an example, the volume ratio of methanol to water in the mixed solution of methanol and water can be 0.5: 1, 1: 1, 1.5: 1, 2: 1, 3: 1, 4: 1, 5: 1.
[0118] In some embodiments, the ratio of the volume of the second solvent to the sum of the mass of the manganese source, the cobalt source, and the zinc source is (0.01-0.5) L: 1 g. As an example, the ratio of the volume of the second solvent to the sum of the mass of the manganese source, the cobalt source, and the zinc source may be 0.01 L: 1 g, 0.05 L: 1 g, 0.08 L: 1 g, 0.1 L: 1 g, 0.2 L: 1 g, 0.3 L: 1 g, 0.4 L: 1 g, 0.5 L: 1 g.
[0119] In some embodiments, the above reaction is carried out at a pressure of 0.05 MPa to 0.2 MPa. As an example, the reaction pressure may be 0.05 MPa, 0.1 MPa, 0.15 MPa or 0.2 MPa.
[0120] In some embodiments, the reaction temperature is 20° C. to 50° C. As an example, the reaction temperature may be 20° C., 30° C., 40° C. or 50° C.
[0121] In some embodiments, the reaction time is 1 h to 24 h. As an example, the reaction time can be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h, 24 h.
[0122] In some embodiments, step S1-2 further includes the following steps:
[0123] After the reaction is completed, the reaction solution is centrifuged, washed and dried to obtain the MnCoZn-ZIF material.
[0124] Optionally, the drying temperature is 50° C. to 90° C. As an example, the drying temperature may be 50° C., 60° C., 70° C., 80° C. or 90° C.
[0125] Optionally, the drying time is 4 h to 10 h. As an example, the drying time may be 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, or 10 h.
[0126] Optionally, during the washing process, any one of ethanol and methanol is used as the washing liquid.
[0127] Optionally, the number of washings is 2 to 5 times.
[0128] Optionally, washing is performed by ultrasonic cleaning.
[0129] In some embodiments, the intermediate material includes nitrogen-doped porous carbon on which Co nanoparticles and Mn nanoparticles are loaded.
[0130] In some embodiments, the catalyst includes nitrogen-doped porous carbon, Co3O4 nanoparticles and MnO2 nanoparticles are loaded on the nitrogen-doped porous carbon, and the Co3O4 nanoparticles are hollow structures.
[0131] Understandably, nanoparticles refer to ultrafine particles with a size between 1 nm and 100 nm. Hollow structure, also known as hollow structure, refers to a material or particle with a cavity inside. Further, in the present invention, the Co3O4 nanoparticles are hollow structures, which means that the Co3O4 nanoparticles have a cavity inside.
[0132] The catalyst in the above-mentioned embodiment uses nitrogen-doped porous carbon as a carrier, and Co3O4 nanoparticles and MnO2 nanoparticles can be uniformly and firmly loaded on the nitrogen-doped porous carbon, so that the catalyst has the advantages of large specific surface area, multiple active sites and good stability. Moreover, the above-mentioned nitrogen-doped porous carbon carrier has abundant micropores, which is beneficial to improve the mass transfer efficiency of reactants on the catalyst surface and the accessibility of catalytic active sites. At the same time, the nitrogen atoms in the nitrogen-doped porous carbon can also effectively activate oxygen, which is beneficial to further improve the catalytic oxidation activity of the catalyst. More importantly, under the joint action of Co3O4 nanoparticles and MnO2 nanoparticles, the catalytic oxidation activity of the catalyst can also be significantly improved. Therefore, under the synergistic action of nitrogen-doped porous carbon, Co3O4 nanoparticles and MnO2 nanoparticles, the catalyst can be ensured to have excellent catalytic activity and stability while reducing the content of Co3O4 nanoparticles.
[0133] Furthermore, in the above-mentioned catalyst, the Co3O4 nanoparticles have a hollow structure, which can expose more catalytic active sites, provide a suitable reaction site for the reactants, and thus improve the catalytic activity of the catalyst and the mass transfer rate of the reactants.
[0134] Optionally, the average particle size of the Co3O4 nanoparticles is 9 nm to 16 nm. As an example, the average particle size of the Co3O4 nanoparticles may be 9 nm, 9.5 nm, 10 nm, 10.5 nm, 11 nm, 11.5 nm, 12 nm, 12.5 nm, 13 nm, 13.5 nm, 14 nm, 14.5 nm, 15 nm, 15.5 nm, 16 nm, or may be within the range consisting of any two of the above point values as end values, optionally 10 nm to 15 nm. When the average particle size of the Co3O4 nanoparticles is 9 nm to 16 nm, there is no obvious agglomeration of the Co3O4 nanoparticles, and they can be more firmly loaded on the nitrogen-doped porous carbon support and are not easy to fall off, thereby effectively improving the catalytic activity and structural stability of the catalyst.
[0135] Optionally, the average particle size of the MnO2 nanoparticles is 9 nm to 16 nm. As an example, the average particle size of the MnO2 nanoparticles may be 9 nm, 9.5 nm, 10 nm, 10.5 nm, 11 nm, 11.5 nm, 12 nm, 12.5 nm, 13 nm, 13.5 nm, 14 nm, 14.5 nm, 15 nm, 15.5 nm, 16 nm, or may be within the range consisting of any two of the above point values as end values, optionally 10 nm to 15 nm. When the average particle size of the MnO2 nanoparticles is 9 nm to 16 nm, there is no obvious agglomeration of the MnO2 nanoparticles, and they can be more firmly loaded on the nitrogen-doped porous carbon carrier and are not easy to fall off, so they can more effectively cooperate with the Co3O4 nanoparticles to enhance the catalytic activity of the catalyst.
[0136] In some embodiments, the average particle size of the Co3O4 nanoparticles is 9 nm to 16 nm, and the average particle size of the MnO2 nanoparticles is 9 nm to 16 nm. Understandably, the average particle sizes of the Co3O4 nanoparticles and the MnO2 nanoparticles are each independently selected from 9 nm to 16 nm. The two nanoparticles of the above-mentioned specific average particle size can not only independently exert excellent catalytic performance, but also have a good synergistic catalytic effect between the two, which can further improve the performance of the catalyst.
[0137] It should be noted that the average particle size of the Co3O4 nanoparticles can be measured by transmission electron microscopy (TEM), and the average value of at least 20 nanoparticle size measurements is taken as the final average particle size. It is understandable that the average particle size can also be measured by other standard or common test methods.
[0138] Optionally, the mass percentage of Co in the catalyst is 25 wt% to 35 wt%. It is understandable that Co in the catalyst mainly exists in the form of Co3O4, and the mass percentage of Co in the above catalyst refers to the mass percentage of Co in Co3O4, which can be measured by general testing methods such as plasma emission spectroscopy or atomic absorption spectroscopy. As an example, the mass percentage of Co in the catalyst may be 25 wt%, 25.29 wt%, 25.5 wt%, 26 wt%, 26.5 wt%, 26.9 wt%, 27 wt%, 27.23 wt%, 27.43 wt%, 27.52 wt%, 27.53 wt%, 27.68 wt%, 27.83 wt%, 28 wt%, 28.36 wt%, 28.5 wt%, 29 wt%, 29.5 wt%, 30 wt%, 30.5 wt%, 31 wt%, 31.5 wt%, 32 wt%, 32.5 wt%, 33 wt%, 33.42 wt%, 33.5 wt%, 34 wt%, 34.5 wt%, 35 wt%, or it may be within the range consisting of any two of the above point values as end values, optionally 25.29 wt% to 33.42 wt%. When the mass percentage of Co in the catalyst is 25 wt% to 35 wt%, the Co content of the catalyst can be as low as possible while ensuring the catalytic performance, thereby reducing the raw material cost.
[0139] Optionally, the mass percentage of Mn in the catalyst is 3.5 wt% to 12 wt%. It is understandable that the Mn in the catalyst is mainly present in the form of MnO2, and the mass percentage of Mn in the above catalyst refers to the mass percentage of Mn in MnO2, which can be measured by common testing methods such as plasma emission spectroscopy or atomic absorption spectroscopy. As an example, the mass percentage of Mn in the catalyst may be 3.5 wt%, 3.89%, 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, 8 wt%, 8.02 wt%, 8.19 wt%, 8.28 wt%, 8.32 wt%, 8.27 wt%, 8.34 wt%, 8.45 wt%, 8.53 wt%, 8.5 wt%, 9 wt%, 9.5 wt%, 10 wt%, 10.5 wt%, 11 wt%, 11.23 wt%, 11.5 wt%, 12 wt%, or it may be within the range consisting of any two of the above-mentioned point values as end values, optionally 3.89 wt% to 11.23 wt%. When the mass percentage of Mn in the catalyst is 3.5 wt% to 12 wt%, the synergistic catalytic effect between Co3O4 nanoparticles and MnO2 nanoparticles can be fully exerted, which is beneficial to improving the catalytic performance of the catalyst.
[0140] Optionally, the catalyst has a specific surface area of 410 m 2 / g~470 m 2 / g. As an example, the specific surface area of the catalyst can be 410 m 2 / g, 413 m 2 / g, 415 m 2 / g, 420 m 2 / g, 425 m 2 / g, 430 m 2 / g, 435 m 2 / g, 440 m 2 / g, 445m 2 / g, 450 m 2 / g, 455 m 2 / g, 460 m 2 / g, 465 m 2 / g, 466 m 2 / g, 470 m 2 / g, or any two of the above points can be used as the end value within the range, optionally 413 m 2 / g~466 m 2 / g. The specific surface area of the catalyst is 410 m 2 / g~470 m2 / g, the mass transfer rate of the reactants can be increased, thereby improving the catalytic activity.
[0141] In a third aspect, the present invention further provides use of the catalyst of the first aspect or the catalyst prepared by the preparation method of the second aspect in catalytic oxidation of carbon monoxide.
[0142] The above-mentioned catalyst has the advantages of low cost, large specific surface area, multiple active sites, high catalytic oxidation activity and good stability. When used for the catalytic oxidation of carbon monoxide, it can oxidize carbon monoxide into carbon dioxide more quickly and thoroughly, which is of great significance for the effective purification of carbon monoxide exhaust.
[0143] In the following examples of the present invention, unless otherwise specified, the materials and instruments used are commercially available, the equipment used is conventional equipment, and the data obtained are the average values of more than three repeated experiments.
[0144] Example 1
[0145] A catalyst comprises nitrogen-doped porous carbon, on which Co3O4 nanoparticles and MnO2 nanoparticles are loaded, wherein the Co3O4 nanoparticles are hollow structures.
[0146] In this embodiment, the average particle size of the Co3O4 nanoparticles is 10.5 nm.
[0147] In this embodiment, the mass percentage of Co in the catalyst is 27.83 wt%, and the mass percentage of Mn is 8.27 wt%.
[0148] In this embodiment, the specific surface area of the catalyst is 462 m 2 / g.
[0149] A method for preparing the catalyst in the above embodiment of the present invention comprises the following steps:
[0150] (1) Preparation of MnCoZn-ZIF materials
[0151] (1.1) Dissolve 3.44 g of 2-methylimidazole (42 mmol) in 90 mL of methanol and stir for 10 min to obtain a first solution. Dissolve 3.57 g of zinc nitrate hexahydrate (12 mmol), 1.22 g of cobalt nitrate hexahydrate (4.2 mmol), and 0.21 g of manganese nitrate tetrahydrate (0.84 mmol) in 180 mL of a mixed solution of methanol and water (the volume ratio of methanol to water in the mixed solution is 1:1) and stir for 10 min to obtain a second solution.
[0152] (1.2) The first solution and the second solution were mixed, and the mixture was stirred at 25 °C and 0.1 MPa for 2 h. The reaction solution was centrifuged to obtain a solid crude product. The solid crude product was then washed with methanol for three times and dried at 80 °C for 8 h to obtain a MnCoZn-ZIF material.
[0153] (2) Preparation of intermediate materials
[0154] 0.5 g of MnCoZn-ZIF material was placed in a quartz boat and dispersed evenly. The quartz boat was then placed in a tube furnace and argon was introduced. The boat was then heated to 900 °C at a heating rate of 5 °C / min and maintained for 2.5 h for the first calcination treatment. The boat was then cooled to room temperature to obtain an intermediate material.
[0155] In this embodiment, the intermediate material includes nitrogen-doped porous carbon, and the nitrogen-doped porous carbon is loaded with Co nanoparticles and Mn nanoparticles.
[0156] (3) Preparation of catalyst
[0157] Air was introduced into the tubular furnace, and the temperature was heated to 400°C at a heating rate of 2°C / min and maintained for 3 h to calcine the intermediate material for the second time. The intermediate material was then cooled to room temperature and the obtained black solid was taken out of the tubular furnace to obtain the catalyst of Example 1.
[0158] In this embodiment, the prepared catalyst includes nitrogen-doped porous carbon, on which Co3O4 nanoparticles and MnO2 nanoparticles are loaded, and the Co3O4 nanoparticles are hollow structures.
[0159] In another embodiment, in step (3), before the intermediate material is subjected to a second calcination, the following treatment is further included: washing the intermediate material with a hydrochloric acid solution having a pH value of 3 to fully remove the metal zinc nanoparticles remaining in the intermediate material, which is beneficial to increase the micropore content and specific surface area of the obtained catalyst, thereby facilitating the improvement of the mass transfer rate of the catalytic reaction.
[0160] An application of the catalyst prepared in the above embodiment in the catalytic oxidation of carbon monoxide is to use the catalyst of the present invention to treat carbon monoxide tail gas to oxidize the carbon monoxide in the tail gas into carbon dioxide.
[0161] Example 2
[0162] A method for preparing a catalyst is substantially the same as the method for preparing the catalyst in Example 1, except that the amount of manganese nitrate tetrahydrate added is 0.105 g (0.42 mmol), and other process conditions are as shown in Table 1.
[0163] The catalyst prepared in Example 2 is substantially the same as the catalyst prepared in Example 1, with the differences shown in Table 2.
[0164] Example 3
[0165] A method for preparing a catalyst is substantially the same as the method for preparing the catalyst in Example 1, except that the amount of manganese nitrate tetrahydrate added is 0.316 g (1.26 mmol), and other process conditions are as shown in Table 1.
[0166] The catalyst prepared in Example 3 is substantially the same as the catalyst in Example 1, with the differences shown in Table 2.
[0167] Example 4
[0168] A method for preparing a catalyst is basically the same as the method for preparing the catalyst in Example 1, except that the amount of zinc nitrate hexahydrate added is 6.25 g (21 mmol), and other process conditions are shown in Table 1.
[0169] The catalyst prepared in Example 4 is substantially the same as the catalyst in Example 1, with the differences shown in Table 2.
[0170] Example 5
[0171] A method for preparing a catalyst is basically the same as the method for preparing the catalyst in Example 1, except that the amount of zinc nitrate hexahydrate added is 2.50 g (8.4 mmol), and other process conditions are shown in Table 1.
[0172] The catalyst prepared in Example 5 is substantially the same as the catalyst in Example 1, with the differences shown in Table 2.
[0173] Example 6
[0174] A method for preparing a catalyst is basically the same as the method for preparing the catalyst in Example 1, except that the temperature of the first calcination is 800° C. and other process conditions are shown in Table 1.
[0175] The catalyst prepared in Example 6 is substantially the same as the catalyst in Example 1, with the differences shown in Table 2.
[0176] Example 7
[0177] A method for preparing a catalyst is basically the same as the method for preparing the catalyst in Example 1, except that the temperature of the first calcination is 1000° C. and other process conditions are shown in Table 1.
[0178] The catalyst prepared in Example 7 is substantially the same as the catalyst in Example 1, with the differences shown in Table 2.
[0179] Example 8
[0180] A method for preparing a catalyst is basically the same as the method for preparing the catalyst in Example 1, except that the temperature of the second calcination is 250° C., and other process conditions are shown in Table 1.
[0181] The catalyst prepared in Example 8 is substantially the same as the catalyst in Example 1, with the differences shown in Table 2.
[0182] Example 9
[0183] A method for preparing a catalyst is basically the same as the method for preparing the catalyst in Example 1, except that the temperature of the second calcination is 500° C. and other process conditions are as shown in Table 1.
[0184] The catalyst prepared in Example 9 is substantially the same as the catalyst in Example 1, with the differences shown in Table 2.
[0185] Example 10
[0186] A method for preparing a catalyst is basically the same as the method for preparing the catalyst in Example 1, except that the second calcination time is 2 h, and other process conditions are shown in Table 1.
[0187] The catalyst prepared in Example 10 is substantially the same as the catalyst in Example 1, with the differences shown in Table 2.
[0188] Embodiment 11
[0189] A method for preparing a catalyst is basically the same as the method for preparing the catalyst in Example 1, except that the second calcination time is 5 h, and other process conditions are shown in Table 1.
[0190] The catalyst prepared in Example 11 is substantially the same as the catalyst in Example 1, with the differences shown in Table 2.
[0191] Comparative Example 1
[0192] A method for preparing a catalyst is substantially the same as the method for preparing the catalyst in Example 1, except that manganese nitrate tetrahydrate is not added, and other process conditions are as shown in Table 1.
[0193] The catalyst prepared in Comparative Example 1 is substantially the same as the catalyst in Example 1, with the differences being shown in Table 2.
[0194] Comparative Example 2
[0195] A method for preparing a catalyst is substantially the same as the method for preparing the catalyst in Example 1, except that zinc nitrate hexahydrate is not added. Other process conditions are shown in Table 1.
[0196] The catalyst prepared in Comparative Example 2 is substantially the same as the catalyst in Example 1, with the differences shown in Table 2.
[0197] Comparative Example 3
[0198] A method for preparing a catalyst is basically the same as the method for preparing the catalyst in Example 1, except that the temperature of the first calcination is 700° C., and other process conditions are shown in Table 1.
[0199] The catalyst prepared in Comparative Example 3 is substantially the same as the catalyst in Example 1, with the differences shown in Table 2.
[0200] Comparative Example 4
[0201] A method for preparing a catalyst is basically the same as the method for preparing the catalyst in Example 1, except that the temperature of the first calcination is 1200° C. and other process conditions are shown in Table 1.
[0202] The catalyst prepared in Comparative Example 4 is substantially the same as the catalyst in Example 1, with the differences shown in Table 2.
[0203] Comparative Example 5
[0204] A method for preparing a catalyst is basically the same as the method for preparing the catalyst in Example 1, except that the temperature of the second calcination is 200° C. and other process conditions are shown in Table 1.
[0205] The catalyst prepared in Comparative Example 5 is substantially the same as the catalyst in Example 1, with the differences shown in Table 2.
[0206] Comparative Example 6
[0207] A method for preparing a catalyst is basically the same as the method for preparing the catalyst in Example 1, except that the temperature of the second calcination is 600° C. and other process conditions are shown in Table 1.
[0208] The catalyst prepared in Comparative Example 6 is substantially the same as the catalyst in Example 1, with the differences shown in Table 2.
[0209] Comparative Example 7
[0210] A method for preparing a catalyst is basically the same as the method for preparing the catalyst in Example 1, except that the first calcination is not performed, and the MnCoZn-ZIF material is directly calcined in air at 400°C for 3 h. Other process conditions are shown in Table 1.
[0211] The catalyst prepared in Comparative Example 7 is substantially the same as the catalyst in Example 1, the main difference being that the Co3O4 in the obtained catalyst does not have a hollow structure. Other differences are shown in Table 2.
[0212] Comparative Example 8
[0213] A method for preparing a catalyst comprises the following steps:
[0214] 1.3 g of nitrogen-doped activated carbon (commercially available), 3.57 g of zinc nitrate hexahydrate (12 mmol), 1.22 g of cobalt nitrate hexahydrate (4.2 mmol) and 0.21 g of manganese nitrate tetrahydrate (0.84 mmol) were added to 180 mL of a mixed solution of methanol and water in a volume ratio of 1:1, stirred for 2 h, filtered and dried to obtain a composite material. The composite material was calcined in argon at 900 ° C for 2.5 h, and then calcined in air at 400 ° C for 3 h after cooling to obtain the catalyst of Comparative Example 8.
[0215] The catalyst prepared in Comparative Example 8 is substantially the same as the catalyst in Example 1, the main difference being that the micropore content in the obtained catalyst is lower. Other differences are shown in Table 2.
[0216] The main preparation parameters in Examples 1-11 and Comparative Examples 1-8 are shown in Table 1, wherein A represents the molar ratio of manganese ions in the manganese source to cobalt ions in the cobalt source, and B represents the molar ratio of cobalt ions in the source to zinc ions in the zinc source.
[0217] Table 1 Main preparation parameters in Examples 1-11 and Comparative Examples 1-8
[0218]
[0219] Each embodiment and comparative example was tested, and the specific test method is as follows:
[0220] (1) XRD
[0221] The prepared samples of Example 1, Example 8 and Example 9 were tested using a D8 Advance X-ray diffractometer (XRD) from Bruker. The specific steps are as follows: the sample was ground, placed in the groove of the sample stage and pressed into a thin sheet, and then tested. The test used Cu Ka rays as the diffraction source, the operating voltage was 40 kV, the current was 40 mA, the incident wavelength was 1.5418 Å, the test conditions were scanning 1 º / min, and the step length was 0.02 º / step. The results are shown in Figure 2. Figure 1 shown.
[0222] (2) SEM
[0223] The surface microstructure of the sample in Example 1 was observed using a Hitachi SU8220 field emission scanning electron microscope (SEM). Test sample processing steps: a small amount of sample was dispersed in anhydrous ethanol, then dropped on conductive glass, placed in an oven for drying, then gold-sprayed, and finally the sample was observed and the corresponding electron microscope images were taken. The results are shown in Figure 2. Figure 2 shown.
[0224] (3) TEM
[0225] The internal structure of the sample in Example 1 was observed using a transmission electron microscope (TEM) model JEM-2100F from JEOL Ltd. Test sample processing steps: Take a small amount of sample and disperse it in anhydrous ethanol, then drop it on a copper mesh and place it in an oven for drying. Use the JEM-2100F transmission electron microscope to obtain a picture of the sample Co3O4 nanoparticles at a higher magnification. The results are as follows: Figure 3 shown.
[0226] In addition, the particle sizes of Co3O4 nanoparticles in various embodiments and comparative examples were statistically analyzed by TEM, and the results are shown in Table 2. (4) ICP
[0227] The content of metal elements (Co, Mn and Zn) in each embodiment and comparative example was determined using an inductively coupled plasma atomic emission spectrometer (ICP) of Optima 8300 manufactured by PerkinElmer Inc. Test sample processing steps: Weigh a certain amount of sample and place it in a 25 mL volumetric flask, add an excess of fresh aqua regia to completely dissolve it, and dilute to the scale with deionized water. The results are shown in Table 2.
[0228] (5) Nitrogen adsorption and desorption test
[0229] The specific surface area and pore size distribution of each embodiment and comparative example were analyzed using a nitrogen adsorption-desorption surface analyzer model ASAP 2460 of Micromeritics. Test sample processing steps: 100 mg of sample was pre-degassed under vacuum at 423 K for 12 h, and then tested at 77 K to obtain the BET specific surface area. The results are shown in Table 2.
[0230] (6) CO catalytic oxidation test
[0231] 0.2 g of the catalyst of each embodiment and comparative example was taken to perform CO catalytic oxidation test. The specific test method was as follows: the CO concentration was controlled to be 2500 ppm, and the rest was air; the air velocity was controlled to be 150000 h -1First, the temperature was raised to 250 °C at a programmed temperature of 10 °C / min, and only air was introduced during the temperature increase process; then CO reaction gas was introduced and maintained at 250 °C for 30 min; finally, the temperature was programmed at 5 °C / min and catalysts T50 and T99 were evaluated, and the results are shown in Table 3. Among them, T50 represents the reaction temperature corresponding to the CO conversion rate of 50%, and T99 represents the reaction temperature corresponding to the CO conversion rate of 99%.
[0232] Figure 1 The XRD patterns of the catalysts prepared in Example 1, Example 8 and Example 9 of the present invention are shown in FIG. Figure 1 It can be seen that the characteristic peaks in the catalysts of Example 1, Example 8 and Example 9 are consistent with the standard diffraction peaks of Co3O4, indicating that the catalyst prepared by the present invention contains Co3O4. Figure 1 It can be seen that compared with the catalyst prepared in Example 1, the characteristic peak intensity of the catalyst prepared in Example 8 is lower. This is because in the preparation method of Example 8, the temperature of the second calcination is low, the oxidation is incomplete, and the content of Co3O4 nanoparticles in the obtained catalyst is low; in addition, the characteristic peak intensity of the catalyst prepared in Example 9 is also slightly reduced. This is because in the preparation method of Example 9, the temperature of the second calcination is high, and the Co3O4 nanoparticles begin to agglomerate. In addition, due to the low content of MnO2 nanoparticles in the catalyst, no obvious characteristic peaks can be observed in the XRD spectrum.
[0233] Figure 2 is a SEM image of the catalyst prepared in Example 1 of the present invention. Figure 2 It can be seen that the catalyst obtained in Example 1 has a dodecahedral structure and is relatively uniform in size, indicating that after the first calcination and the second calcination, the catalyst can still maintain the polyhedral structure of the MnCoZn-ZIF material.
[0234] Figure 3 TEM image of Co3O4 nanoparticles in the catalyst prepared in Example 1 of the present invention. Figure 3 It can be seen that the Co3O4 nanoparticles in the catalyst obtained in Example 1 have a hollow structure (ie, the portion within the white dotted circle), and the particle size is about 10 nm.
[0235] Table 2 Performance indicators of the catalysts prepared in Examples 1-11 and Comparative Examples 1-8
[0236]
[0237] Table 3 Test results of the catalysts prepared in Examples 1-11 and Comparative Examples 1-8 for CO catalytic oxidation
[0238]
[0239] The test results are analyzed in combination with Table 2 and Table 3, as follows:
[0240] The T50 of the catalysts prepared in Examples 1 to 11 is not more than 100°C, and the T99 is less than 160°C, which indicates that the catalysts prepared in the present invention have good CO catalytic oxidation activity.
[0241] Compared with Example 1, T50 and T99 of Comparative Example 1 and Examples 2 to 3 all increased, wherein Comparative Example 1 did not add tetrahydrate manganese nitrate, and the obtained catalyst did not contain MnO2, indicating that MnO2 in the catalyst obtained in Example 1 can have a synergistic catalytic effect with Co3O4, which can improve the catalytic performance of the catalyst. In addition, the manganese content in the catalyst obtained in Example 2 is relatively low, and the synergistic catalytic effect is not obvious, so T50 and T99 are both higher than Example 1, that is, the catalytic performance is slightly lower than that of Example 1. In Example 3, too much tetrahydrate manganese nitrate was added, and the hexahydrate cobalt nitrate was relatively small, so the cobalt content in the catalyst was low, and the catalytic activity was worse than that of Example 1. In summary, if the molar ratio of manganese ions to cobalt ions in the raw material is too high or too low, it will affect the performance of the obtained catalyst. Based on this, in the present invention, by further regulating the molar ratio of manganese ions to cobalt ions in the raw material to 0.15 to 0.25: 1, the performance of the catalyst can be more effectively improved.
[0242] Compared with Example 1, T50 and T99 of Comparative Example 2 and Examples 4 to 5 all increased, wherein Comparative Example 2 did not add zinc nitrate hexahydrate, the micropore content of the obtained catalyst was less, the specific surface area was lower, and the nanoparticles in the catalyst agglomerated, the particle size was larger, so the catalytic performance was poor; in Example 4, too much zinc nitrate hexahydrate was added, the micropores formed in the obtained catalyst collapsed, and the content of the micropores was reduced, so its catalytic activity was not as good as that of Example 1. In Example 5, too little zinc nitrate hexahydrate was added, the nanoparticles agglomerated, and the micropores formed in the obtained catalyst were less, so its catalytic performance was not as good as that of Example 1. In summary, if the molar ratio of zinc ions to cobalt ions in the raw materials is too high or too low, the performance of the catalyst will be affected. Based on this, in the present invention, by further regulating the molar ratio of zinc ions to cobalt ions in the raw materials to be 0.3 to 0.4:1, the performance of the catalyst can be effectively improved.
[0243] Compared with Example 1, T50 and T99 of Comparative Examples 3 to 4 both showed a significant increase, indicating that the temperature of the first calcination is too high or too low, which is not conducive to improving the performance of the catalyst. Based on this, the present invention can improve the performance of the catalyst by regulating the temperature of the first calcination within the range of 800°C to 1000°C. Furthermore, T50 and T99 of Examples 6 to 7 are also higher than those of Example 1, indicating that controlling the temperature of the first calcination at 850°C to 950°C can more effectively improve the performance of the catalyst.
[0244] Compared with Example 1, T50 and T99 of Comparative Examples 5 to 6 both showed a significant increase, indicating that the temperature of the second calcination is too high or too low, which is not conducive to improving the performance of the catalyst. Based on this, the present invention can effectively improve the performance of the catalyst by regulating the temperature of the second calcination within the range of 250 ℃ to 500 ℃. Further, T50 and T99 of Examples 8 to 11 are also higher than those of Example 1, indicating that controlling the temperature of the second calcination at 350 ℃ to 450 ℃ and the time at 2 h to 5 h can more effectively improve the performance of the catalyst. Compared with Example 1, T50 and T99 of Comparative Example 7 both showed a significant increase. Comparative Example 7 did not undergo the first calcination, and the micropore content in the obtained catalyst was less, the specific surface area was lower, and the Co3O4 nanoparticles did not have a hollow structure, so the performance was significantly deteriorated, which shows that the present invention can form Co3O4 nanoparticles with a hollow structure by calcining twice, thereby improving the performance of the obtained catalyst.
[0245] Compared with Example 1, T50 and T99 of Comparative Example 8 both increased significantly. In Comparative Example 8, nitrogen-doped activated carbon was used instead of nitrogen-doped porous carbon prepared with MnCoZn-ZIF as a precursor. The specific surface area of the obtained catalyst was significantly reduced, and the catalytic performance was significantly deteriorated. This shows that the present invention uses MnCoZn-ZIF as a raw material to obtain a nitrogen-doped porous carbon carrier with abundant micropores and a large specific surface area, which is beneficial to improving the mass transfer rate of reactants such as CO in the catalyst, thereby improving the performance of the catalyst.
[0246] It can be seen from the above results that compared with traditional Co-based catalysts, the catalyst of the present invention, under the synergistic effect of nitrogen-doped porous carbon, Co3O4 nanoparticles with a hollow structure and MnO2 nanoparticles, can ensure that the catalyst has excellent catalytic activity while reducing the content of Co3O4 nanoparticles. It has the advantages of low cost, large specific surface area, many active sites, high catalytic oxidation activity, good stability, etc. When used for the catalytic oxidation of carbon monoxide, it can oxidize carbon monoxide into carbon dioxide more quickly and thoroughly, which is of great significance for achieving effective purification of carbon monoxide tail gas.
[0247] The above embodiments are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A catalyst, characterized in that The invention comprises nitrogen-doped porous carbon, on which Co3O4 nanoparticles and MnO2 nanoparticles are loaded; the Co3O4 nanoparticles are hollow structures; and the preparation method of the catalyst comprises the following steps: (1) Preparation of MnCoZn-ZIF materials; (2) calcining the MnCoZn-ZIF material for the first time in an inert atmosphere at a temperature of 800° C. to 1000° C. to obtain an intermediate material; (3) The intermediate material is subjected to a second calcination in an oxygen-containing atmosphere at a temperature of 250° C. to 500° C. to obtain a catalyst.
2. The catalyst according to claim 1, characterized in that The average particle size of the Co3O4 nanoparticles is 9 nm to 16 nm.
3. The catalyst according to claim 1 or 2, characterized in that The catalyst also satisfies at least one of the following conditions (1.1) to (1.3): (1.1) The mass percentage of Co in the catalyst is 25 wt% to 35 wt%; (1.2) The mass percentage of Mn in the catalyst is 3.5 wt% to 12 wt%; (1.3) The specific surface area of the catalyst is 410 m 2 / g~470 m 2 / g.
4. A method for preparing a catalyst, characterized in that: The following steps are involved: S1. preparing MnCoZn-ZIF material; S2, calcining the MnCoZn-ZIF material for the first time in an inert atmosphere at a temperature of 800° C. to 1000° C. to obtain an intermediate material; S3. The intermediate material is calcined for a second time in an oxygen-containing atmosphere at a temperature of 250°C to 500°C to obtain a catalyst; the catalyst comprises nitrogen-doped porous carbon, on which Co3O4 nanoparticles and MnO2 nanoparticles are loaded; and the Co3O4 nanoparticles are hollow structures.
5. The preparation method according to claim 4, characterized in that: The method for preparing the catalyst also satisfies at least one of the following conditions (2.1) to (2.6): (2.1) The temperature of the first calcination is 850°C to 950°C; (2.2) The first calcination time is 2 h to 4 h; (2.3) The inert atmosphere includes at least one of nitrogen and argon; (2.4) The temperature of the second calcination is 350°C to 450°C; (2.5) The second calcination time is 2 h to 5 h; (2.6) The oxygen-containing atmosphere includes at least one of oxygen and air.
6. The preparation method according to claim 5, characterized in that: Before the second calcination, the intermediate material is further treated as follows: the intermediate material is washed with an acidic solution; the pH value of the acidic solution is 1-4.
7. The preparation method according to any one of claims 4 to 6, characterized in that In step S1, the method for preparing the MnCoZn-ZIF material comprises the following steps: S1-1, preparing a first solution by combining 2-methylimidazole and a first solvent; preparing a second solution by combining a manganese source, a cobalt source, a zinc source and a second solvent; S1-2, mixing the first solution and the second solution to react, to prepare the MnCoZn-ZIF material.
8. The preparation method according to claim 7, characterized in that: The method for preparing the MnCoZn-ZIF material also satisfies at least one of the following conditions (3.1) to (3.11): (3.1) The molar ratio of manganese ions in the manganese source to cobalt ions in the cobalt source is 0.15 to 0.25:1; (3.2) The molar ratio of cobalt ions in the cobalt source to zinc ions in the zinc source is 0.3 to 0.4:1; (3.3) The molar ratio of the 2-methylimidazole to the cobalt ions in the cobalt source is 5 to 20:1; (3.4) The manganese source includes at least one of manganese nitrate tetrahydrate, manganese sulfate monohydrate and manganese acetate trihydrate; (3.5) The cobalt source includes at least one of cobalt nitrate hexahydrate and cobalt acetate tetrahydrate; (3.6) The zinc source includes at least one of zinc nitrate hexahydrate and zinc acetate dihydrate; (3.7) The first solvent includes at least one of methanol, ethanol and water; (3.8) The second solvent includes at least one of methanol, ethanol and water; (3.9) The reaction is carried out at a pressure of 0.05 MPa to 0.2 MPa; (3.10) The reaction temperature is 20 ℃ to 50 ℃; the reaction time is 1 h to 24 h; (3.11) After the reaction is completed, the following treatment is further included: the reaction solution obtained by the reaction is centrifuged, washed and dried to obtain the MnCoZn-ZIF material.
9. The preparation method according to claim 8, characterized in that: In step S2, the intermediate material includes nitrogen-doped porous carbon, and the nitrogen-doped porous carbon is loaded with Co nanoparticles and Mn nanoparticles.
10. Use of the catalyst according to any one of claims 1 to 3 or the catalyst prepared by the preparation method according to any one of claims 4 to 9 in catalytic oxidation of carbon monoxide.
Citation Information
Patent Citations
Preparation method and application of hollow structure Co3O4 / CeO2 nanoparticle loaded nitrogen doped carbon nanofiber material
CN110124713A
Cobalt-copper binary metal oxide catalyst for catalytic combustion of VOCs gas and preparation method of cobalt-copper binary metal oxide catalyst
CN117718047A